A Study Of Succession Planning Implementation In Malaysia - Chan, Hun Pin (2004)
The implementation of succession planning has drawn significant attention from the global business firms especially after the September 11 tragedy. More firms acknowledge that there is a must to get successors ready to replenish top position when they are gone. There is a need also to develop a better understanding of how the incumbent's propensity to step aside and the presence of competent successor in influencing the implementation of succession planning in Malaysia context despite many researches have been done in foreign countries.